2022
DOI: 10.3390/children9071049
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Radial Neck Fractures: A Systematic Review Regarding the Influence of Fracture Treatment on Elbow Function

Abstract: Background: This review aims to identify what angulation may be accepted for the conservative treatment of pediatric radial neck fractures and how the range of motion (ROM) at follow-up is influenced by the type of fracture treatment. Patients and Methods: A PRISMA-guided systematic search was performed for studies that reported on fracture angulation, treatment details, and ROM on a minimum of five children with radial neck fractures that were followed for at least one year. Data on fracture classification, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…However, Falciglia et al ( 22 ) suggested that immobilization is not always necessary if the radial head is stable after surgery, but Langenberg et al ( 23 ) concluded that non-fixed fractures have a higher percentage of loss of range of motion after surgery. If the radius neck fracture Angle is greater than 60°, the use of Kirschner wire fixation after closed reduction may have an advantage over elastic intramedullary nail fixation, but this difference is not significant in fractures angled at 31°–60°.…”
Section: Discussionmentioning
confidence: 99%
“…However, Falciglia et al ( 22 ) suggested that immobilization is not always necessary if the radial head is stable after surgery, but Langenberg et al ( 23 ) concluded that non-fixed fractures have a higher percentage of loss of range of motion after surgery. If the radius neck fracture Angle is greater than 60°, the use of Kirschner wire fixation after closed reduction may have an advantage over elastic intramedullary nail fixation, but this difference is not significant in fractures angled at 31°–60°.…”
Section: Discussionmentioning
confidence: 99%
“…Reducción cerrada: es la primera opción en casos de alto desplazamiento y angulación, se recomienda realizarla bajo sedación y fluoroscopia. En caso de no obtener una reducción adecuada en varios intentos, se recomienda pasar a otro método de tratamiento 7 . Reducción percutánea: se recomienda en casos de alto grado de angulación y desplazamiento, pero con contacto entre la cúpula y la metáfisis.…”
Section: Tratamiento Quirúrgicounclassified
“…One frequent cause of a fat pad sign is a radial neck fracture. Langenberg and colleagues [ 19 ] systematically reviewed the literature on pediatric radial neck fractures, particularly on the influence of fracture treatment on range of motion after at least 1 year. In total, 26 studies with a total of 551 children were included.…”
mentioning
confidence: 99%